Strategi Guru dalam Mengelola Kelas melalui Pendekatan Outdoor Learning yang Efektif di SD Alam Ungaran Semarang - Setiyorini, Nunung Dwi; Suprihatma, Suprihatma (Paedagogie, 2026)
This study aims to describe teacher strategies for managing classrooms through an effective outdoor learning approach at SD Alam Ungaran Semarang and to identify challenges and solutions in its implementation. This study used a qualitative approach with a case study method. The subjects were teachers selected using a purposive sampling method. Data collection techniques included semi-structured interviews, participant observation, and documentation. Data analysis was conducted through data reduction, data presentation, and conclusion drawing, while maintaining data validity through triangulation and member checking. The results showed that teachers implemented a planned classroom management strategy through positive discipline, utilizing the environment as a contextual learning medium, managing the outdoor learning environment, strengthening teacher-student relationships, and varying learning methods. These strategies were able to create a conducive learning atmosphere, increase student engagement, and maintain engagement during learning outside the classroom. The conclusions of this study confirm that the outdoor learning approach can function effectively as a classroom management strategy if systematically designed and implemented by teachers. Contains: Research Objectives; Research Methods; Data Collection & Analysis; Results; Conclusions.